Performance determinants for emerging agricultural cooperatives in South Africa - Komape, Kwena (Graduate School of Business (GSB), 2019)
South Africa has seen an increase in the number of cooperatives (co-ops) registered since 2005, following the new policy aimed at the promotion of cooperative enterprises. Newly registered co-ops received over R5.28 billion in direct financial support, comprising a combination of grants and loans from government. Over and above the financial support, co-ops also receive non-financial support in the form of capacity development. Some of the co-ops received support in the form of inputs and farming equipment. In spite of the support that government provides to emerging co-ops, the majority remain vulnerable and weak. This study seeks to establish the factors that determine the performance of emerging agricultural cooperatives in South Africa. In order to attain this, data were obtained from the Cooperative Data Analysis System (CODAS) of the Department of Agriculture Forestry and Fisheries. Cooperatives considered for the study have been in operation for at least five years by 2017. Results of the Spearman’s correlation used to analyse the results indicate that membership, wages, training and number of years in operation have a significant impact on the dependent variable, turnover. The main limitation of the study is the use of turnover alone as a measure of performance, due to limited data. Other variables such as growth in membership could be used as additional measures of performance; however, the numbers per cooperative in the study are constant throughout the observations.